Hydroxyl porous aromatic frameworks for efficient adsorption of organic micropollutants in water. Issue 44 (14th July 2020) - Mo, Chen; Faheem, Muhammad; Aziz, Saba; Jian, Song; Xue, Wang; Yuyang, Tian; Shuang, Ding; Guangshan, Zhu
Abstract : A series of hydroxyl functionalized PAF materials (PAF-80, PAF-81, and PAF-82) were synthesized, which create polar channels to the hydrophobic surfaces and explored as efficient adsorption of organic micropollutants in water. Abstract : Environmental pollution is an important issue in sustainable human development. People give great importance to environmental protection, especially with regards to increasingly scarce water resources. Water pollution is becoming more and more serious due to the existence of organic micropollutants. As a platform with good stability, porous aromatic frameworks (PAFs) have been widely studied. Because of their high surface area and thermal stability, they are considered to be a good sewage treatment agent. However, the aromatic nature of PAFs makes their skeletons mostly hydrophobic. This characteristic of PAFs seriously affects their diffusion rate in water as an adsorbent, resulting in a low adsorption rate. In this work, we synthesized a series of hydroxyl functionalized porous aromatic frameworks (PAF-80, PAF-81, and PAF-82) via the Sonogashira–Hagihara cross-coupling reaction, which created polar motifs on the hydrophobic surfaces, and carried out adsorption tests on typical organic micropollutants in water such as bisphenol A (BPA), 2-naphthol (2-NO) and p -chloroxylenol (PCMX). Among the three PAFs, PAF-82 exhibited the highest BET surface area, polar active sites, and a high degree of conjugation, which led to the best adsorption performance compared to that of PAF-80 and PAF-81. The Langmuir adsorption capacity of PAF-82 for BPA, 2-NO, and PCMX is 689 mg g −1, 431 mg g −1, and 480 mg g −1, respectively, which surpasses most previously reported adsorbents. In addition, after 5 cycles of regeneration, it still maintained a high removal rate for pollutants. The obtained results reveal that micropollutant adsorption in water is not controlled by a single factor, but is the result of a synergy of multiple factors, including specific surface area, polar functional groups, pore size distribution, and skeleton conjugation. Our study has revealed the great potential of hydroxyl PAFs for efficient adsorption of organic micropollutants in water.